Voyage into savage Europe : a declining civilization - Hameiri, Avigdor, 1890-1970 (Academic Studies Press, 2020)
"In this unique memoir, now in English for the first time, Israel's first Poet Laureate Avigdor Hameiri details a trip to Europe in 1930 from the perspective of a Hungarian Jew who had served in the Habsburg Army. Upon visiting Austria, Hungary, Romania (including parts of ceded Hungarian Transylvania), and Czechoslovakia (including his Carpatho-Ruthenian homeland), he sees Europe in flux on the brink of an unknown disaster. Austria and Hungary are full of youth whose philosophy is "eat, drink and be merry; tomorrow we die." There is fear of Bolshevism from without, but the unfelt danger is German Fascism. Jews (especially in Hungary) are assimilated but cannot escape from their Jewishness: some are Zionists. Romania is corrupt and antisemitic. In Carpatho-Ruthenia, Hameiri has two premonitions warning him to return to Israel, a prediction of the destruction soon to befall Europe. Hameiri also gives accounts of the artistic and cultural scenes of 1930s Europe, as well as the world of Carpatho-Ruthenian Hasidism, which was soon to be destroyed by the Holocaust. From the growing danger and confusion surrounding inter-war Europe, in prose at once compassionate and bitingly sarcastic, comes a sweeping account of Jewish life in 1930 from one of Israel's prolific writers"--